2018
DOI: 10.1038/aps.2018.40
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, cardiovascular diseases and type 2 diabetes mellitus

Abstract: Leptin, an adipokine that is implicated in the control of food intake via appetite suppression, may also stimulate oxidative stress, inflammation, thrombosis, arterial stiffness, angiogenesis and atherogenesis. These leptin-induced effects may predispose to the development of cardiovascular diseases. In the present review we discuss the evidence linking leptin levels with the presence, severity and/or prognosis of both coronary artery disease and non-cardiac vascular diseases such as stroke, carotid artery dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(183 citation statements)
references
References 212 publications
8
161
0
14
Order By: Relevance
“…Leptin, a vital hormone derived from adipose tissue, plays a significant role in various pathways prompting the risk of diabetes and cardiovascular diseases (Patel et al, 2016;Katsiki et al, 2018). In current study, diabetes induction by alloxan significantly increased (P≤0.05) leptin concentration in serum, while a significant decrease in serum leptin level (P≤0.05) was observed in high protein diet group.…”
Section: Discussionsupporting
confidence: 45%
“…Leptin, a vital hormone derived from adipose tissue, plays a significant role in various pathways prompting the risk of diabetes and cardiovascular diseases (Patel et al, 2016;Katsiki et al, 2018). In current study, diabetes induction by alloxan significantly increased (P≤0.05) leptin concentration in serum, while a significant decrease in serum leptin level (P≤0.05) was observed in high protein diet group.…”
Section: Discussionsupporting
confidence: 45%
“…Ryan et al [20] found that leptin could lead to vascular dysfunction by directly acting on LEPR. In addition, some studies also confirmed that the serum leptin level increased in patients with diabetes, indicating its involvement in the occurrence and development of diabetic vascular complications [21] . Wu et al [6] showed that hydrogen sulfide could inhibit the HG-induced injury in HUVECs through inhibiting leptin/LEPR.…”
Section: Discussionmentioning
confidence: 88%
“…Ryan et al [22] found that leptin could lead to vascular dysfunction by directly acting on LEPR. In addition, some studies also confirmed that the serum leptin level increased in patients with diabetes, indicating its involvement in the occurrence and development of diabetic vascular complications [23] . Wu et al [6] showed that hydrogen sulfide could inhibit the HG-induced injury in HUVECs through inhibiting leptin/LEPR.…”
Section: Discussionmentioning
confidence: 88%